Bicycle Urbanism. Reimagining Bicycle Friendly Cities. - (:unkn) unknown (Routledge, 2018)
The book emerged from the Bicycle Urbanism Symposium held at the University of Washington in Seattle in June 2013. It aks the question "How du we design cities for bicycles?" The symposium brought together practitioners, academics, policy makers, and advocates with diverse backgrounds including urban design, planning, transportation, engineering, landscape architecture, public policy and advocacy.
Keywords: Urbaner Raum; Fahrradverkehr; Fahrradinfrastruktur; Stadtplanung; Nachhaltigkeit; Best Practice; Neue Technologie; Stadtentwicklungskonzept; Transport; Demokratisierung